Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Ekonomi Menggunakan Metode Ceramah dan Diskusi Kelompok pada SMA Negeri 1 Katingan Hilir: Improving Learning Outcomes of Students in Economic Learning Using Lecture Methods and Group Discussions at Katingan Hilir 1 Public High School - Berliani, Erni; Nurbudiyani, Iin (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to determine the learning activities of students and find out the improvement in student learning outcomes. The type of this research is Classroom Action Research (CAR) with research subjects of all students of class X-7 of SMAN 1 Katingan Hilir, amounting to 24 students. Data collection techniques in this study used tests and observations. Data analysis uses qualitative and quantitative data analysis. The results of this study indicate that: (1) the use of lecture methods and group discussions on economic subjects are more active students which are shown by the acquisition of scores above 3, (2) the use of lecture methods and group discussions on economic issues can improve learning outcomes students demonstrated by obtaining an average rating of 61.25 in the first cycle increased to 80 in the second cycle. Classical learning completeness also increased with a value of 50% in the first cycle increased to 87.5% in the second cycle.